Oral Health Impact on Ventilator-Associated Pneumonia - Bailey Miles; Sarah Beth Tanner; Krystal Herring, RDH, MPH (Elsevier, 2024)
OBJECTIVES: Evaluate the role oral hygiene plays in decreasing the risk of contracting Ventilator-Associated Pneumonia (VAP) for patients on life-support. METHODS: Five different research studies were used to measure the effectiveness of various mouthwashes ability to prevent VAP. The mouthwashes evaluated were Clove mouthwash, Ozonated Water (OZW), Chlorohexidine Gluconate (CHG), and Povidone Iodine. For each study, the patients were split into a control and experimental group. All patients were treated with the designated mouthwash, using a mouth swab for application. There was a variation of the duration of each study, as well as the time intervals of mouthwash application. The studies were conducted over the course of anywhere from a few hours to several days. There were numerous data collection instruments used throughout each study to measure the incidence of VAP contraction, such as Acute Physiology and Chronic Health Evaluation II (APACHEII), The Beck Oral Assessment Scale (BOAS), and Modified Clinical Pulmonary Infection Score (MCPIS). RESULTS: • Study One: 40% participants in Chlorohexidine group contracted VAP; double that of the Clove Extract group • Study Two: 9 out of 36 patients in OZW group contracted VAP; 17 out of 37 patients in CHG group contracted VAP • Study Three: Experimental group showed an overall reduction in bacterial growth • Study Four: 0% VAP contraction in experimental group; 10.58% contraction in control group • Study Five: 10 patients in CHG group contracted VAP; 17 patients in placebo group contracted VAP CONCLUSIONS: Overall, this literature review confirms that mouthwash solutions do have a positive effect in the reduction of VAP in critically ill patients. However, research has not consistently shown one solution to be more triumphant than another, when compared. IMPLICATIONS: In a hospital setting the findings influence clinical dentistry by showing the importance of providing professional cleanings within 24 hours of mechanical ventilation, providing oral care using an antibacterial mouthwash 3 times a day, and ensuring that patients teeth are brushed twice a day. In a private practice setting the findings show the importance/need of advocating for patients receiving proper oral care while in a critically ill state and spreading awareness on the effect that oral hygiene has on preventing VAP.